Development of HOTS-Based Mathematics Module Integrating Lubuklinggau Tourism Context to Improve Students' Mathematical Literacy - Lucy Asri Purwasi; Rani Refianti; Evanni Daniswara Haryono; Idul Adha (AL-ISHLAH: Jurnal Pendidikan, 2025)
Mathematical literacy among university students remains low, partly due to the lack of contextualized teaching materials that support higher-order thinking skills (HOTS). This study aims to develop a HOTS-based mathematics module integrating the tourism context of Lubuklinggau to improve students' mathematical literacy. The study employed a research and development (RD) approach using the 4-D model (Define, Design, Develop, Disseminate). Participants included first-semester PGSD students at Universitas PGRI Silampari, comprising 6 students in small group testing and 31 students in field testing. Instruments included expert validation forms, practicality questionnaires, and a mathematical literacy test. Data were analyzed using descriptive quantitative techniques. Validation results showed the module was considered valid (content: 80%, media: 80%, language: 89%). Practicality assessments from lecturers (87%) and students (97%) indicated the module was highly usable. The module effectively improved students’ mathematical literacy, with an average score of 80.31%, classified as "very effective." All assessed indicators—communication, problem-solving strategies, mathematization, representation, and reasoning—achieved either effective or very effective categories. The integration of local tourism context within a HOTS framework offers a promising strategy to enhance students' engagement and comprehension. The developed module not only meets the criteria of validity, practicality, and effectiveness but also serves as a relevant instructional tool for supporting 21st-century skills in mathematics education.